A Critique of some criticisms of the works of Jane Austen - Mannaf, Alveera (College of Arts and Letters, University of the Philippines Diliman, 1989)
This is the study of some of the criticisms of the works of Jane Austen, the six novels in particular. Jane Austen's works were very popular in the early 19th century. Many have criticized her works as being too light and fivolous taking into account the poverty that was quite rampant in England during that time. Then were the horrifying effects of the Napoleonic Wars. We do not see any traces of such happenings in her books. She wrote about a limited number of character in the limited community of the landed gentry in the villages, who seemed to be untouched by the troubles of that time. Because of this may prominent writers of her time questioned the importance of her work. A deeper study of criticisms, for and against. Jane Austen's works in perspective with her life and her upbringing will quite clearly show us why she wrote as she did and which would precisely be the reason for their popularity. It will also show us that the deceptive lightness of spirit is actually an ironical depiction of the landed gentry during that time, too immersed in themselves to be touched by real life and its tribulations.